RISK FACTOR CONTROL IN PATIENTS WITH CORONARY HEART DISEASE – RESIDENTS OF A NORTH CAUCASUS REGION - R. T. Didigova; Z. Ugurchieva; A. M. Inarokova; M. N. Mamedov (Российский кардиологический журнал, 2011)
Aim. To analyse how effectively the three main risk factors – arterial hypertension (AH), hypercholesterolemia, and Type 2 diabetes mellitus (DM-2) are controlled among male and female patients with coronary heart disease (CHD), who are residents of the Ingush Republic. Material and methods. The study included 300 men and 230 women (mean age 54±0,4 and 55,7±0,5 years, respectively) – residents of the three Ingush Republic regions. The standard questionnaire included items on sociodemographic parameters, behavioural risk factors, and pharmaceutical therapy. Blood pressure (BP) was measured in a sitting position, with a 5-minute interval between two measurements. In all patients, blood levels of total cholesterol (TCH, mmol/l)) and glucose (mmol/l) were measured. Adequate control of AH, hypercholesterolemia, and DM-2 was defined as the achievement of target levels of BP, TCH, and fasting glucose during the treatment. Results. Among CHD patients, hypercholesterolemia was the most prevalent risk factor in both men (95%) and women (81%). Only 11,3% of men and 21% of women received lipid-lowering therapy (typically, statins). Target TCH levels were achieved in 1% and 2%, respectively. AH was registered in 77,3% and 65% of male and female CHD patients, respectively. In men with CHD and AH, 93% received antihypertensive therapy (18%, 49%, and 26% received one, two, or three medications, respectively). Target BP levels were observed in 43% of the treated men. In women with CHD and AH, 28%, 60%, and 7% received one, two, or three antihypertensive medications, respectively; target BP levels were achieved in 49%. DM-2 prevalence reached 17% in men and 13% in women. Among patients with CHD and DM-2, target fasting glucose levels were registered in 41% of men and 21% of women. Conclusion. Among CHD patients, target BP levels were achieved in every second participant, while target glucose levels were observed in 30%, and target TCH concentrations were registered in less than 2%.